PENGARUH GAYA KEPEMIMPINAN DAN EVALUASI KINERJA TERHADAP PRESTASI KERJA DI UPTD PUSKESMAS CIANJUR KABUPATEN CIANJUR - Sumiati, Imas (Decision, 2021)
Abstarct Based on the results of research and observations conducted by researchers at the Cianjur Community Health Center, Cianjur Regency, the main problem in this study is low work performance. It is suspected that it is due to the low performance evaluation and leadership style given by the Puskesmas. Allegedly due to the still low performance evaluation given by the Puskesmas. This research was conducted using a quantitative quasi method. Research methods to examine certain theories that already exist by examining the relationships between variables. The variables in this quantitative study were measured using a research instrument which then the research data were in accordance with statistical procedures. This study uses theories about leadership styles, performance evaluation, work performance and theories related to research. Constraints faced in performance evaluation with work performance in Cianjur Health Center in Cianjur Regency are the timeliness in providing services at the Cianjur Health Center in Cianjur, lack of readiness of employees in helping people who are confused and do not understand the flow of the existing system. Efforts to overcome it, namely the Cianjur Public Health Center, Cianjur Regency needs to have a performance evaluation every week, month, and year, especially in the field of health services so that employees help people who are confused and do not understand the flow of the existing system. Keywords: Performance Evaluation, Job Performance, Service Officers